Implementation of Wireless Sensor Network as Data Communication Media in Remote Monitoring Systems (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
This study focuses on the implementation of Wireless Sensor Networks (WSNs) as a communication medium that is becoming an increasingly relevant technological solution for remote monitoring because it is capable of transmitting real-time data without cable infrastructure, especially in areas that are difficult to reach or dangerous for humans. This study aims to test the performance of WSNs as a data communication medium in remote monitoring systems by assessing transmission quality and power consumption efficiency in various environmental conditions. This research is an experimental quantitative study with testing in three different environmental scenarios (open, semi-obstructed, and enclosed concrete) during a period of periodic data transmission. The parameters measured include delay, packet loss, throughput, sensor accuracy, and node power consumption. The study shows that the environment greatly affects network performance, with open areas producing an average delay of 210 ms, semi-obstructed areas 287 ms, and concrete-enclosed areas 403 ms, while the highest packet loss occurred in enclosed areas at 6.4%. The highest throughput was recorded in open areas at 0.245 Mbps. Relay nodes consumed 46 mAh per hour, which was higher than regular nodes. WSN has proven to be effective as a remote data monitoring communication medium for small packet delivery, even though its performance is affected by physical environmental conditions. Further research is recommended to evaluate routing optimization and renewable energy sources to extend the operational life of nodes.
Keywords: Keywords: Wireless Sensor Network, Remote Monitoring, Delay, Packet Loss, Throughput.